Developing a management framework for income generating Waqf properties: case study of Kuala Lumpur - Bello, Hafis; Sarkawi, Azila; Ayob, Mohd Fairullazi (2019)
Previous researches have shown that many Waqf properties are poorly maintained thereby resulting the report low income from these properties. (A. Mohsin and M. Mohammad, 2011). With the increased investment in waqf development, there is clear need to put in place a framework to that will help waqf managers maintain these developments.